Solid-state compound phase formation of TiSi2 thin films under stress - C. Theron; N. Mokoena; O. Ndwandwe (South African Journal of Science)
Different stress situations were created on an Si(100) wafer by depositing either Si3N4 or SiO2 thin films on the back side. Si3N4 has a different thermal expansion coefficient from that of SiO2. A thin Ti film was then deposited on the front side of the Si wafer. The structures were then annealed at various high temperatures for different periods of time. Real-time Rutherford backscattering spectrometry, as well as sample curvature measurements, were used to characterise the samples. Different reaction rates were found between Si3N4-deposited samples and SiO2-deposited samples.